Oxygen isotopes in terrestrial gastropod shells track Quaternary climate change in the American Southwest. (November 2021) - Rech, Jason A.; Pigati, Jeffrey S.; Springer, Kathleen B.; Bosch, Stephanie; Nekola, Jeffrey C.; Yanes, Yurena
Abstract: Recent studies have shown the oxygen isotopic composition (δ 18 O) of modern terrestrial gastropod shells is determined largely by the δ 18 O of precipitation. This implies that fossil shells could be used to reconstruct the δ 18 O of paleo-precipitation as long as the isotopic system, including the hydrologic pathways of the local watershed and the gastropod systematics, is well understood. In this study, we measured the δ 18 O values of 456 individual gastropod shells collected from paleowetland deposits in the San Pedro Valley, Arizona that range in age from ca. 29.1 to 9.8 ka. Isotopic differences of up to 2‰ were identified among the four taxa analyzed (Succineidae, Pupilla hebes, Gastrocopta tappaniana, and Vallonia gracilicosta ), with Succineidae shells yielding the highest values and V . gracilicosta shells exhibiting the lowest values. We used these data to construct a composite isotopic record that incorporates these taxonomic offsets, and found shell δ 18 O values increased by ~4‰ between the last glacial maximum and early Holocene, which is similar to the magnitude, direction, and rate of isotopic change recorded by speleothems in the region. These results suggest the terrestrial gastropods analyzed here may be used as a proxy for past climate in a manner that is complementary to speleothems, but potentially with much greater spatial coverage.